Enhanced electrochemical performance of ZnMoO4/reduced graphene oxide composites as anode materials for lithium-ion batteries. (20th December 2016) - Xue, Ruinan; Hong, Wei; Pan, Zeng; Jin, Wei; Zhao, Huilin; Song, Yahui; Zhou, Jingkuo; Liu, Yu
Highlights: Irregular plate-like ZnMoO4 crystals are first used as anode materials for lithium-ion batteries. ZnMoO4 crystals wrapped by reduced graphene oxide (rGO) sheets are synthesized by a facile hydrothermal method. The rGO can improve the conductivity of ZnMoO4 /rGO composites. The rGO sheets can shorten the length of lithium ions diffusion paths. Abstract: ZnMoO4 /reduced graphene oxide composites (ZnMoO4 /rGO) were successfully prepared by a simple one-pot hydrothermal method, in which the synthesis of ZnMoO4 irregular plate-like crystals and the reduction of graphene oxide to rGO were simultaneously achieved. The XRD, SEM, TEM, TGA and XPS measurements were performed to illustrate the structure properties of as-prepared ZnMoO4 and ZnMoO4 /rGO. It has been demonstrated that the ZnMoO4 /rGO composites exhibits excellent electrochemical performance of high capacity and good stability as the anode materials of lithium-ion batteries. The initial discharge capacity is 2391.2 mAh g −1 at a current density of 100 mA g −1 . During the cycle performance test, the discharge capacity increased from the second cycle capacity of 1030 mAh g −1 to 1454.4 mAh g −1 after 26 cycles at 100 mA g −1 . And after 100 cycles, the retention of capacity is 61.36%. The advanced electrochemical performance can be attributed to the introduction of rGO sheets, which could greatly increase the conductivity of active materials and provide the electrons transfer paths for the ZnMoO4 /rGO electrode. Besides, the rGO sheet wrapped ZnMoO4 crystals would buffer the volume changes during charge-discharge cycles.